2016
DOI: 10.1056/nejmoa1511049
|View full text |Cite
|
Sign up to set email alerts
|

Serious Asthma Events with Fluticasone plus Salmeterol versus Fluticasone Alone

Abstract: Patients who received salmeterol in a fixed-dose combination with fluticasone did not have a significantly higher risk of serious asthma-related events than did those who received fluticasone alone. Patients receiving fluticasone-salmeterol had fewer severe asthma exacerbations than did those in the fluticasone-only group. (AUSTRI ClinicalTrials.gov number, NCT01475721.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
101
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(111 citation statements)
references
References 25 publications
4
101
1
5
Order By: Relevance
“…The add-on therapy with salmeterol resulted in significantly more favorable outcomes in terms of PEF change from baseline, the need for rescue medication, and the number of symptom-free days [76,77]. Recent multicenter, randomized, double-blind studies showed that treatment with budesonide/formoterol and fluticasone/salmeterol were associated with a lower risk of asthma exacerbations than budesonide alone and fluticasone alone groups respectively [78,79]. There have been concerns about the safety of LABA use in patients with asthma [80,81], but patients who received the ICS/LABA combination preparations did not have a significantly higher risk of serious asthma-related events than did those who received ICS alone.…”
Section: Safety and Efficacymentioning
confidence: 99%
“…The add-on therapy with salmeterol resulted in significantly more favorable outcomes in terms of PEF change from baseline, the need for rescue medication, and the number of symptom-free days [76,77]. Recent multicenter, randomized, double-blind studies showed that treatment with budesonide/formoterol and fluticasone/salmeterol were associated with a lower risk of asthma exacerbations than budesonide alone and fluticasone alone groups respectively [78,79]. There have been concerns about the safety of LABA use in patients with asthma [80,81], but patients who received the ICS/LABA combination preparations did not have a significantly higher risk of serious asthma-related events than did those who received ICS alone.…”
Section: Safety and Efficacymentioning
confidence: 99%
“…62 The risk of asthma exacerbation was significantly reduced in patients who continued ICS-LABA (hazard ratio 0.76, 0.65 to 0.91). Of note, the results from these studies are derived primarily from adults.…”
Section: Summary Of Step-down Choicesmentioning
confidence: 98%
“…However, contrary to expectations, adding a long-acting beta 2 agonist has surprisingly little effect on the use of reliever inhalers. 9 After asthma has been well-controlled for 2-3 months, treatment can be gradually stepped down to find the patient's minimum effective dose.…”
Section: Book a Review Visit If Treatment Has Been Started Or Changedmentioning
confidence: 99%